Significant Bradycardia in Critically Ill Patients Receiving Dexmedetomidine and Fentanyl - Channing Hui; Maria Cardinale; Balaji Yegneswaran (Case Reports in Critical Care)
Purpose. To report a case series of three patients who developed significant bradycardia while receiving the combination of dexmedetomidine and fentanyl for sedation and analgesia. Materials and Methods. This is a case series of patients obtained from a mixed medical, surgical, and cardiac ICU in a community teaching hospital. Three intubated patients receiving fentanyl and dexmedetomidine infusion developed sudden bradycardia requiring intervention. In all three cases, adjustments to therapy were required. Results. All three patients experienced significant bradycardia, with a heart rate less than 50 bpm, and one patient briefly developed asystole. In Case  1, the fentanyl infusion rate was reduced by 67% and the dexmedetomidine infusion rate was reduced by 25%. In Case  2, the sedation was changed to midazolam, and in Case  3, both fentanyl and dexmedetomidine were discontinued. In all three cases, there were no further incidences of significant bradycardia following intervention. Conclusions. Fentanyl used in combination with dexmedetomidine can result in clinically significant bradycardia. Further study is warranted to identify risk factors and elucidate the mechanisms that result in life-threatening bradycardia.